Immunophenotypes in Acute Lymphoblastic Leukemia; association with Demographic Profile and Clinical Presentation - Naeem, Samina (International Journal of Pathology, 2018)
Objective: This study was carried out to determine the frequency of B lymphoblastic leukemia (B-ALL)and T lymphoblastic leukemia (T-ALL) in Acute Lymphoblastic Leukemia (ALL) patients in our populationand to observe their association with the demographic profile and clinical features at presentation.Study Design: Non randomized prospective study.Place and duration of study: King Edward Medical University, Lahore and Hameed Latif Hospital,Lahore; from Feburary 2013 to March 2014.Methodology: Fifty newly diagnosed and untreated patients of ALL were selected from Mayo Hospitaland Hameed Latif Hospital. They included both genders and all age groups. Relevant history and findingsof physical examination were recorded.Immunophenotyping was done on bone marrow samples by 5 colour flowcytometery on Beck ManCoulter Navious flowcytometer. An acute leukemia panel of 23 antibodies was used. The data was enteredand analyzed in SPSS version 22.Results: Of the 50 ALL patients 36(72%) were B-ALL and 14(28%) T-ALL. There were 18(36%) childrenand 32(64%) adults. T-ALL included 4(22%) of the childhood and 10(31%) of the adult cases. Male: Femaleratio was 4:1 in total patients, 2:1 in children and 7:1 in adults. A significant preponderance of TALLwas seen in the age cohort of 15 to 25 years. No association was observed between ALL immunophenotypesand gender or the presenting clinical features.Conclusion: The frequency of T-ALL is higher and the male predominance is greater in childhood aswell as adult ALL in our population compared to the Western literature. Although T-ALL is significantlyhigher in the adolescents and young adults, it is not associated with male gender or organomegaly